Resolução de problemas: possíveis relações entre raciocínio lógico e desempenho em Matemática - Kramm, Daniele de Lima (2014)
In education, there has been concern in developing problem-solving behavior as one of the responsibilities of the school, whose task includes that of providing students with procedures to enable them to meet the challenges of contemporary life. The present study had problem solving as its central theme and aimed at identifying and understanding possible relationships between performance on tasks involving logical thinking and mathematics performance. To this end, subjects were 12 children aged 8 and 9 years old which attended the third year of elementary school - of a public school in the city of São Paulo. The instrument for data gathering was composed by12 questions involving problems without number, 12 problems with and without possible solution, 36 problems with some sort of logical violation (12involvingcausal violations, 12 implied temporal violations and 12 consisted of general violations). The subjects responded to the 60 problems whose correctness criterion required that the answer was in the predicted direction and was accompanied by proper justification, obtained by the inquiry provoked by the researcher. The following procedures for data analysis were performed by: 1. Individual performance on each problem; 2.Analysis of the relative difficulty of each question in each type of problem (depending on the number of hits obtained in them); 3.Analysis of the justifications; 4.Analysis of performance for classification of students (previously classified as strong or weak performers on mathematics), and 5. Performing Statistical using Minitab Statistical Software testing. It was possible to identify relationship between mathematics performance and behavior in solving logical problems